203. Opportunities for Antimicrobial Stewardship in Febrile Neutropenia. (31st December 2020) - Shoff, Christopher; Baskett, Jordan; Messina, Julia A; Baker, Arthur W; Turner, Nicholas A; Spivey, Justin; Wrenn, Rebekah; Moehring, Rebekah W; Spires, Steven S
Abstract: Background: Emerging evidence suggests antibiotics may be safely discontinued before neutropenia resolves in patients without identifiable infection. We estimated the volume of encounters and antibiotic use for future stewardship interventions shortening FN treatment duration. Methods: This retrospective cohort study used electronic health records from inpatient encounters on the hematologic malignancies ward at Duke University Hospital from 5/21/2018 to 12/31/2019 where patients received at least one antibiotic for an indication of "neutropenic fever." The primary outcome was length of therapy (LOT) of broad Gram-negative (GN) agents, including cefepime, piperacillin-tazobactam, meropenem, or aztreonam. FN LOT was counted by calendar day, starting with the first day of administration of a broad GN agent and ending with antibiotic discontinuation or hospital discharge. Encounters with at least one positive blood culture (positive cohort) were compared to those with no positive blood cultures (negative cohort) to assess if culture positivity was associated with differences in FN LOT. We included the first FN LOT from each encounter in the negative cohort and the FN LOT associated with the first positive blood culture in the positive cohort. We used descriptive statistics and a Gaussian density function to calculate the percent of encounters exceeding FN LOT of 14 days and the percent of broad GN agent days. Results: We evaluated 15, 678 GN antibiotic administrations from 471 unique FN encounters. Blood culture results were available for 443 encounters— 122 (27.5%) in the positive cohort, and 321 (72.5%) encounters in the negative cohort. Thirty percent of encounters (36/122) in the positive cohort received more than one GN treatment course, compared to 10% (32/321) of those in the negative cohort. FN LOT was significantly longer in the positive cohort (median 10.5, IQR 13 days vs. 6, IQR 8 days, p < 0.001). Among encounters with negative cultures, 57 (17.8%) had a first FN LOT greater than 14 days, accounting for 44% of broad GN agent days within that population (Figure 1). Gram-Negative Antibiotic Therapy in Blood Culture-Negative Febrile Neutropenia Conclusion: Nearly 20% of blood culture-negative encounters received initial GN treatment courses exceeding 14 days, representing a sizeable target for antimicrobial stewardship interventions focused on FN treatment duration. Disclosures: Rebekah W. Moehring, MD, MPH, Agency for Healthcare Quality and Research (Grant/Research Support)Centers for Disease Control and Prevention (Grant/Research Support)